2023
DOI: 10.1158/1078-0432.ccr-22-2550
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Lethal Interaction with BCL-XL Blockade Deepens Response to Cetuximab in Patient-Derived Models of Metastatic Colorectal Cancer

Abstract: Purpose: Approximately 20% of patients with RAS wild-type metastatic colorectal cancer (mCRC) experience objective responses to the anti-EGFR antibody cetuximab, but disease eradication is seldom achieved. The extent of tumor shrinkage correlates with long-term outcome. We aimed to find rational combinations that potentiate cetuximab efficacy by disrupting adaptive dependencies on anti-apoptotic molecules (BCL2, BCL-XL, MCL1). Experimental Design: Experiments were conducted in patient-derived xenografts (PDXs)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…PDOs #6 and #7 were established as previously described. 52 Organoids were tested for Mycoplasma and maintained at 37°C in a humidified atmosphere of 5% CO2. All the PDOs were cultured in Cultrex Basement Membrane Extract (BME) Type 2 (Amsbio) with ENAS medium.…”
Section: Methodsmentioning
confidence: 99%
“…PDOs #6 and #7 were established as previously described. 52 Organoids were tested for Mycoplasma and maintained at 37°C in a humidified atmosphere of 5% CO2. All the PDOs were cultured in Cultrex Basement Membrane Extract (BME) Type 2 (Amsbio) with ENAS medium.…”
Section: Methodsmentioning
confidence: 99%
“…Although inhibitors of Bcl-2 and Bcl-xL are effective in treating hematopoietic malignancies [ 17 ], efficacy is limited in primary solid cancers including GC partly because of a complex microenvironment that promotes cancer cell survival and resistance to treatment. Clinical trials of inhibitors of the Bcl-2 family in advanced GC have shown mixed results, and application in GC is currently limited [ 18 , 19 ]. However, a potential window for targeting Bcl-2 family members may arise during metastasis of solid tumors [ 9 ], where circulating tumor cells or colonizing micrometastatic foci maintain a high level of cancer stemness and are less strongly influenced by the microenvironment, with similarities to hematopoietic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…However, a potential window for targeting Bcl-2 family members may arise during metastasis of solid tumors [ 9 ], where circulating tumor cells or colonizing micrometastatic foci maintain a high level of cancer stemness and are less strongly influenced by the microenvironment, with similarities to hematopoietic malignancies. In addition, combining Bcl-2 family inhibition with other strategies can suppress metastasis in solid cancers [ 18 ]. Combination strategies guided by biomarkers to predict the response of inhibitors of the Bcl-2 family in the treatment of metastatic advanced GC have been suggested as a potential solution to the limited effectiveness of these inhibitors in GC.…”
Section: Introductionmentioning
confidence: 99%